Copper Recovery From Ammonia Solutions Through Electro-Electrodialysis (EED) - Garrido, Belen; Cifuentes, Gerardo; Fredes, Pedro; Pino, Eduardo; Calderón, Cristian; Cifuentes-Cabezas, Magdalena (Frontiers in Chemistry, 2021)
Alkaline leaching with highly selective ammoniacal complexing agents is an interesting alternative for the treatment of copper concentrates. This treatment is beneficial for copper recovery because it allows the formation of soluble amines complexes, being the most stable the cupric tetramine ( Cu(NH_3 )_4^(2+)). In order to suppress the unit operation of solvent extraction (SX) and move directly to the electrochemical process, an electro-electrodialysis (EED) process using ion exchange membranes to obtain copper is proposed. The study contemplates the operation with synthetic ammonia solutions containing copper at different concentrations and current density under standard conditions of pressure and temperature. The presented data demonstrates that the concentration of copper in the solution and the excess of ammonia are inversely related to the efficiency of the current and the voltage of the cell, whereas an increase in current density causes an increase in current efficiency, contrary to what happens in sulfuric systems.